Relations between State and Sovereignty in the Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the fundamental relationship between the state and sovereignty, which are the main pillars of the modern political system. Sovereignty provides legitimacy to the state to run a legitimate and effective government, while the state serves as a vessel for implementing that sovereignty. Using perspectives from classical and modern thinkers such as Schmitt, Hobbes, and Fukuyama, the author explores how sovereignty allows the state to act independently and maintain domestic and international stability. In the context of globalisation, challenges to state sovereignty are increasingly complex, including foreign intervention and limitations on state policy due to international agreements. On the other hand, the importance of stable state institutional strength in maintaining sovereignty is increasingly emphasised, especially in facing external threats and domestic conflicts. The relationship between the state and sovereignty can be maintained sustainably by strengthening state institutions, respecting international law, and promoting public participation in politics. In conclusion, a sovereign state must be able to maintain a balance between power and justice to ensure legitimacy and stability in an ever-evolving political order.